Teacher’s preparedness for implementing competency based curriculum in primary schools in Kiambu County, Kenya - Mwabora, Julius; Nyamu, Florence; O'Connor, Marguerite Miheo (Strathmore University, 2019)
This article is based on a study that investigated teachers’ preparedness for implementing the competency-based curriculum in primary schools in Kiambu County, Kenya. The government of Kenya has rolled out the competency-based curriculum (CBC) amid concerns by education stakeholders regarding preparedness of teachers. CBC emphasizes the significance of developing skills, knowledge, and attitudes and applying them to real-life situation. The study measured teachers’ preparedness and readiness regarding teachers technological skills required for the implementation, and teachers perception regarding implementation of the competencybased curriculum. The study involved the use of a descriptive survey design. The research participants included 15 head teachers and 50 primary school teachers. Analysis of the data involved the use of descriptive statistics. Presentation involved the use of figures, frequency tables, and percentages. The study findings indicate that the primary school teachers are not prepared for implementing the competency-based curriculum in the early childhood education and lower primary education. It was evident that the teachers experienced challenges due to limited in-service training, inadequate parental support, inadequate information and communications technology skills, and a heavy workload. Based on the findings, it was recommended that the Ministry of Education need to organize additional in-service training workshops for primary school teachers to impart them with information and communications technology skills, subject content knowledge, and improve teachers’ perceptions regarding competency-based curriculum.
Paper presented at the 5th Strathmore International Mathematics Conference (SIMC 2019), 12 - 16 August 2019, Strathmore University, Nairobi, Kenya
Keywords: Competency-Based Curriculum; Training; Information and Communications Technology